Analysis of Vertical Response of Drilled Pile at the Crest of Rock Slope Based on Shear Behavior. (26th May 2021) - Jiang, Chong; Fang, Ju; Sun, Bowen
Abstract : This paper proposed a method for analysis of a drilled pile under vertical load at the crest of rock slope. Based on wedge theory, a modified model of normal stiffness of socket wall affected by the slope is obtained. Analyze the shear behaviors of the pile-rock interface, an analytical solution of load transfer of pile at the crest of rock slope is obtained. To evaluate the accuracy of the new method, this method is compared with the results of finite difference analysis. Finally, the method is used to analyze the effect of slope, pile, and rock properties on the unit side resistance and axial force.